A friendly fire on economic recovery: A methodology to estimate the costs of data regulations - Erik Van der Marel; Matthias Bauer; Hosuk Lee-Makiyama (European Centre for International Political Economy (ECIPE), 2014)
This background paper describes the methodology used for the ECIPE Occasional Paper called "The Costs of Data Localisation: A Friendly Fire on Economic Recovery" in which the costs of data services regulation are assessed. This paper provides further explanation on how the costs of data regulation affect industries and firms in four different ways. First, we calculate the costs of data regulation for domestic firms by establishing a link between regulation in data services and the level of total factor productivity (TFP) at industry level across countries in downstream sectors. As such, this is the first attempt at analysing this linkage econometrically by setting up a data protection regulation index using a typology of existing indices of services regulation. The regression analysis reveals that data regulation indeed tends to affect TFP in industries which depend more heavily on data processing services. Second, we provide relative cost estimates as a result of data regulation that affects foreign exporting firms for each of the countries and industries considered in this study. This is because foreign firms face upfront investment and operational costs when data regulations are applied by the host government. Third, this paper assesses the costs for investment made in the host country as a consequence of data regulation. Finally, the costs of research and development (R&D) activities which are affected by regulation in data services are also taken into account as constraints on the free flow of data could, in addition, decrease innovation activities by firms. Together these four ways of measuring costs of data regulation are used for a general equilibrium analysis using the Global Trade Analysis Project (GTAP) to estimate the GDP, trade effects and investment costs as presented in the ECIPE study.
Keywords: F13; L86; D24; 330; Data services flows; Productivity; Domestic regulatory barriers